When Doing Nothing is an Option: Self-correction of an Impacted Mandibular Second Premolar. (2nd July 2022) - Aruede, Glenda; Yaqoob, Nasreen; Smart, Keith
Abstract : This case presents a rare example of self-correction of a deeply impacted mandibular second premolar (LR5) in a medically fit 14-year-old male patient, referred in 2017 regarding a retained deciduous lower right second molar (LRe). CBCT imaging highlighted that the origin of the ID canal was in direct contact with the inferior buccal aspect of the LR5 root apex. The decision was made to monitor the patient in 2 years. In the meantime, the dentist extracted the retained LRe as it was seen to be erupting on routine bitewing imaging. At his review appointment, the LR5 had spontaneously erupted. CPD/Clinical Relevance: To highlight the potential benefit of monitoring eruption in the event that high-risk surgery is the alternative option and involving the patient in the decision making.